Does Research on Evaluation Matter? Findings From a Survey of American Evaluation Association Members and Prominent Evaluation Theorists and Scholars. (June 2016) - Coryn, Chris L. S.; Ozeki, Satoshi; Wilson, Lyssa N.; Greenman, Gregory D.; Schröter, Daniela C.; Hobson, Kristin A.; Azzam, Tarek; Vo, Anne T.
Research on evaluation theories, methods, and practices has increased considerably in the past decade. Even so, little is known about whether published findings from research on evaluation are read by evaluators and whether such findings influence evaluators' thinking about evaluation or their evaluation practice. To address these questions, and others, a random sample of American Evaluation Association (AEA) members and a purposive sample of prominent evaluation theorists and scholars were surveyed. A majority of AEA members (80.95% ± 7.60%) and sampled theorists and scholars (84.21%) regularly read research on evaluation and indicate that research on evaluation has influenced their thinking about evaluation and their evaluation practice (97.00% ± 3.38% and 94.00% ± 4.79%, for AEA members, and 100% and 100%, for prominent theorists and scholars, respectively).